Advancement in understanding the role of ferroptosis in rheumatoid arthritis - Long, Li; Guo, Hongmei; Chen, Xixi; Liu, Yan; Wang, Ruyi; Zheng, Xiaomei; Huang, Xiaobo; Zhou, Qiao; Wang, Yi (Frontiers in Physiology, 2022)
Rheumatoid arthritis (RA) is a chronic, systemic disease of unknown etiology. The primary manifestation of RA is inflammatory synovitis, which eventually leads to deformity and functional loss. Ferroptosis is a non-apoptosis form of cell death that depends on intracellular iron accumulation. This leads to an increase in reactive oxygen species (ROS) induced-lipid peroxidation. The underlying mechanisms of ferroptosis are System Xc- and Glutathione metabolism, regulation of glutathione peroxidase 4 activity, and ROS generation. Recent studies have shown an association between the pathogenesis of RA and ferroptosis, suggesting the involvement of ferroptosis in the onset and progression of RA. In this review, we have focused on the mechanism of ferroptosis and its association with RA pathogenesis. Further, we discuss the status of therapeutics targeting ferroptosis in the treatment of patients with RA. Targeting ferroptosis could be a potential therapeutic approach for RA treatment.